Evidence of endogenously produced hydrogen sulfide (H2S) and persulfidation in male reproduction - Řimnáčová, Hedvika; Moravec, Jiří; Štiavnická, Miriama; Havránková, Jiřina; Monsef, Ladan; Hošek, Petr; Prokešová, Šárka; Žalmanová, Tereza; Fenclová, Tereza; Petr, Jaroslav; Králíčková, Milena; Nevoral, Jan (Scientific reports, 2022)
Persulfidation contributes to a group of redox post-translational modifications (PTMs), which arise exclusively on the sulfhydryl group of cysteine as a result of hydrogen sulfide (H2S) action. Redox-active molecules, including H2S, contribute to sperm development; therefore, redox PTMs represent an extremely important signalling pathway in sperm life. In this path, persulfidation prevents protein damage caused by irreversible cysteine hyperoxidation and thus maintains this signalling pathway. In our study, we detected both H2S and its production by all H2S-releasing enzymes (cystathionine γ-lyase (CTH), cystathionine β-synthase (CBS), and 3-mercaptopyruvate sulfurtransferase (MPST)) in male reproduction, including spermatozoa. We provided evidence that sperm H2S leads to persulfidation of proteins, such as glyceraldehyde-3-phosphate dehydrogenase, tubulin, and anchor protein A-kinase. Overall, this study suggests that persulfidation, as a part of the redox signalling pathway, is tightly regulated by enzymatic H2S production and is required for sperm viability.
Keywords: sperma; Semen; sulfan; Hydrogen Sulfide; cystathionin-gama-lyasa; Cystathionine gamma-Lyase; Cysteine; Reproduction; Humans; rozmnožování; mužské pohlaví; Male; lidé; cystein